A new modified FMEA model for ranking the risk of maintenance waste considering hierarchy of root causes and effects. (2015) - Sutrisno, Agung; Gunawan, Indra; Khorshidi, Hadi Akbarzade; Tangkuman, Stenly
Implementing sustainable manufacturing practice requires efficiency of the resource utilisation and activities which add value to the operations. From this point of view, development of an improved methodology to access the criticality of non-added value (waste) is important and believed to support the realisation of sustainable manufacturing operation. While previous studies on improving methodology to support sustainable operation from product and process design are abundantly available in the references, the contribution from maintenance field is in contrary. The goal of this study is to modify the quality improvement tool, failure mode and effect analysis (FMEA) to access the criticality of waste in maintenance operation. In an attempt to realise the above goal, an empirical study to propose the theoretical and actual maintenance waste from industrial practice is undertaken. In order to assist maintenance decision maker to quantify criticality of maintenance waste occurrence, a new model to rank waste maintenance mode, called the waste priority number (WPN) is given. Illustrative on using model for practical purpose is given.